2021
DOI: 10.1097/aog.0000000000004621
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Outcomes After Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection in Vaccinated Compared With Unvaccinated Pregnant Patients

Abstract: BMI, body mass index; HIV, human immunodeficiency virus. Data are mean6standard deviation or n (%) unless otherwise specified. * Table 1 includes the primary analysis; all patients received the full course of the elected vaccine series at least 2 weeks before the start of the study period, with a cutoff date of May 30, 2021 (one dose for Janssen and two doses for mRNA vaccine). N for secondary analysis including both fully and partially vaccinated patients51,536. † Patients of the following races were specifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 6 publications
3
100
0
1
Order By: Relevance
“…10 These studies highlight the importance of further research to continue building evidence to help inform patient counseling and build patient confidence in vaccination administration. Immunization against COVID-19 has been shown to protect against infection related morbidity in pregnant women 15 ; our data support its continued use for pregnant patients.…”
Section: Accepted Manuscriptsupporting
confidence: 67%
“…10 These studies highlight the importance of further research to continue building evidence to help inform patient counseling and build patient confidence in vaccination administration. Immunization against COVID-19 has been shown to protect against infection related morbidity in pregnant women 15 ; our data support its continued use for pregnant patients.…”
Section: Accepted Manuscriptsupporting
confidence: 67%
“…A flowchart of study selection process is reported in Figure 2 . We considered 46 records: 30 of them included pregnant mothers [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], two studies included both pregnant and lactating mothers [ 39 , 40 ], and 14 studies included lactating mothers [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Most studies were conducted in the United States (41.3%) and Israel (26.1%), along with three in Italy (6.5%), two in Spain (4.3%) and in Poland (4.3%), and the remaining (17.2%) in the United Kingdom, Qatar, Belgium, Germany, Norway, Portugal, the Netherlands, and Singapore.…”
Section: Resultsmentioning
confidence: 99%
“…During this period, women in the UK were recommended to shield as they were classed as being clinically vulnerable and SARS-CoV-2 vaccinations for pregnant women were not approved by the Joint Committee on Vaccination and Immunization (JCVI) until April 2021 (29). Maternal vaccination has been found to reduce severity of SARS-CoV-2 infection (30), and should be encouraged. Whilst our cohort of women did not have severe symptoms of COVID-19, despite being unvaccinated, the lack of any associated placental pathology and the minimal changes observed in the number of placental immune cells indicates that mild maternal COVID-19 infection is unlikely to cause harm to the developing fetus.…”
Section: Poor Pregnancy Outcomes and Placental Pathologymentioning
confidence: 99%